COMPARATIVE ANALYSIS OF MORPHOLOGICAL CHARACTERISTICS PIGEON BREEDS - Parés i Casanova, Pere-Miquel (2009)
Relationships among 18 Spanish and Iberoamerican pouter pigeon breeds were studied using data from 28 morphological characteristics based on the parsimony principle by the Fitch method for the qualitative analysis. A cluster dendogram was generated by the minimum variance between Ward groups for the quantitative analysis. Some logic in the trees was found but no clear relationships between breeds were observed. The value of Consistency Index was 0.38 and for the Retention Index was 0.416, indicating a medium fit between data and cladogram. The results showed that some of the morphological characteristics could not be informative or that complementary traits such behavioral ones would give better information in the construction of a logical classification tree for pouter pigeon breeds.